EuroGuiderm guideline on lichen sclerosus: introduction into lichen sclerosus : guidelines - Kirtschig, Gudula; Kinberger, M.; Kreuter, A.; Simpson, R.; Günthert, A.; van Hees, C.; Becker, K.; Ramakers, M. J.; Corazza, M.; Müller, S.; von Seitzberg, S.; Boffa, M. J.; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
Introduction Lichen sclerosus (LS) is an inflammatory skin disease affecting all ages. LS typically involves the anogenital site where it causes itching and soreness. It may lead to sexual and urinary dysfunction in females and males; however, it may be asymptomatic. First signs of LS are redness and oedema, typically followed by whitening of the genital skin; sometimes fissuring, scarring, shrinkage and fusion of structures may follow in its course. LS is associated with an increased risk of genital cancer. LS has a huge impact on the quality of life of affected patients, and it is important to raise more awareness of this not uncommon disease in order to diagnose and treat it early. Objectives The guideline intends to provide guidance on the diagnostic of LS, highlight important aspects in the care of LS patients (part 1), generate recommendations and treatment algorithms (part 2) on topical, interventional and surgical therapy, based on the latest evidence, provide guidance in the management of LS patients during pregnancy, provide guidance for the follow-up of patients with LS and inform about new developments and potential research aspects. Materials and Methods The guideline was developed in accordance with the EuroGuiDerm Methods Manual v1.3 https://www.edf.one/de/home/Guidelines/EDF-EuroGuiDerm.html. The wording of the recommendations was standardized (as suggested by the GRADE Working Group). The guideline development group is comprised of 34 experts from 16 countries, including 5 patient representatives. Results Ultrapotent or potent topical corticosteroids in females and males, adults and children remain gold standard of care for genital LS; co-treatment with emollients is recommended. If standard treatment fails in males, a surgical intervention is recommended, complete circumcision may cure LS in males. UV light treatment is recommended for extragenital LS; however, there is limited scientific evidence. Topical calcineurin inhibitors are second line treatment. Laser treatment, using various wave lengths, is under investigation, and it can currently not be recommended for the treatment of LS. Treatment with biologics is only reported in single cases. Conclusions LS has to be diagnosed and treated as early as possible in order to minimize sequelae like scarring and cancer development. Topical potent and ultrapotent corticosteroids are the gold standard of care; genital LS is often a lifelong disease and needs to be treated long-term.
Erstmals veröffentlicht: 01. Juni 2024
Gesehen am 26.11.2024